CONTEMPORARY ASPECTS IN THE PATHOGENESIS OF BRAIN EDEMA IN PATIENTS WITH HEMORRHAGIC CEREBROVASCULAR INSULT - Rendevska, Ana Mihajlovska; Aleksovski, Boris; Shuntov, Blagoj; Aleksovski, Vasko; Mircevski, Mirko Mishel; Stoev, Viktor; Rendevski, Vladimir (Journal of Morphological Sciences, 2020)
The worst neurological deterioration after hemorrhagic cerebrovascular insult (H-CVI) occurs due to the formation of perihematomal edema, a proven significant risk factor for poor prognosis. During the last several years, a vast number of studies have focused on the pathogenesis of the brain edema.The main objective of this review paper was the evaluation of the biochemical and molecular mechanisms involved in the pathogenesis of the edema, with a special focus on the inflammatory and oxidative mechanisms. We believe that this brief review could serve as a motivational boost for designing a comprehensive clinical study, in which the radiological and clinical variables, as well as the proinflammatory mediators and the oxidative stress markers will be simultaneously evaluated for their predictive roles in the formation of brain edema.  Key words:hemorrhagic cerebrovascular insult, perifocal edema, pathogenesis, proinflammatory mediators, oxidative stress.